THE EFFECT OF ETHANOLIC EXTRACT OF Syzygium cumini LEAVES ON THE GROWTH OF Streptococcus mutans: PENGARUH EKSTRAK ETANOLIK DAUN JAMBLANG (Syzygium cumini) TERHADAP PERTUMBUHAN Streptococcus mutans - Sungkar, Suzanna; Haniastuti, Tetiana; Santoso, Al Supartinah; Agustina, Dewi (TALENTA, 2018)
Streptococcus mutans plays an important role in the pathogenesis of caries. This bacteria has virulence properties involve in the formation of bioï¬lm on tooth surface. Due to its antibacterial effect, Jamblang leaf may be used as an agent to prevent caries. Objective: This study aimed to elucidate the effects of ethanolic extract of Jamblang leaves on the growth of S. mutans. Methods: Analysis of active compounds was carried out using thin layer chromatography (TLC) and Liquid Chromatograph-Mass Spectrography (LC-MS). Samples of S. mutans were isolated from childrenâ€™s carious deciduous molar teeth. Growth test was done by dilusion technique. Aquadest was used as a negative control. Results: TLC and LC-MS showed the presence of the flavonoid, tannin, and terpenoid Kruskall-Wallis test showed significant differences (p<0.05) among the groups, indicating that Jamblang leaves ethanolic extract decreased the growth of S.mutans. The higher concentrations of the extract, the less number of S.mutans colonies grown. No colony of S. mutans at 22.5% of extractâ€™s concentration. Conclusion: Jamblang leaves ethanolic extract reduces the growth of S. mutans. Concentration of 22.5%Jamblang leaves ethanolic extracthas bacteriocid effect. Key words: Ethanolic extract of Jamblang (Syzygium cumini) leaves, growth, Streptococcus mutans